Design of opener shape for improving gimbal tongue shift on y-axis - Warut Klayaubol; Monsak Pimsarn (IOP Conference Series Materials Science and Engineering, 2021)
Abstract There are four necessary components for testing read-write efficiency of Slider, which are [1] Slider electrical testing machine [2] Fixture, a tool for holding Slider while testing [3] Slider to read and write data in hard disk drive and [4] Opener, a mechanism to open a fixture for loading and unloading Slider. The opener should open a fixture only in x direction but it appears that the opener drives a fixture in both x and y directions which results in misalignment of Slider in a fixture. A poor Slider alignment definitely affects a read-write efficiency of Slider. Therefore, this article will show a study of opener shape that relates to fixture behaviour and also a comparison of four designs of opener-arm angle (15 degrees, -15 degrees, -30 degrees and -40 degrees) by using Finite Element Analysis (FEA). Result shows -40 degrees opener is the best one that can open the fixture only in y direction and meets the design requirement.
Keywords: Metal Forming Simulation Techniques; Mechanical stress and fatigue analysis; Metallurgy and Material Forming